Prostat cancer profile in Dr. Sardjito General Hospital Yogyakarta - Yurisal Akhmad Dany; Ahmad Zulfan Hendri; Indrawarman Soerohardjo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Prostate  cancer  is  the  fourth  most  common  type  of  non-skin  malignancy  in  male malignancies. In Indonesia, the definitive data are unreported, however, Globocan  reported  prostate  cancer  in  5th  place  in  2018.    Early  diagnosis  and  treatment  of  this  cancer  are  associated  with  reduced  mortality  rates.  This  study aimed to investigate the profile of prostate cancer in Dr. Sardjito General Hospital,  Yogyakarta,  Indonesia.  A  retrospective  study  involving  a  total  of  90  prostate cancer patients who underwent follow-up care at Dr. Sardjito General Hospital, Yogyakarta in the period of 2015 to 2020 was conducted. Data of the patients from their medical records consisted of age, gender, prostate volume, PSA  level,  testosterone  level,  hydronephrosis,  TURP  history,  histopathology  results,  Gleason  scores,  ISUP  grade,  and  staging  TNM  were  collected.  The  average of patients age was 67 ±10.4 y.o. where 22 (24.4%) patients aged < 60 y.o., 34 (37.8%) patients aged 61-70 y.o. and 34 (37.8%) patients aged >70 y.o. Almost of all patients (87 patients or 97.8%) were diagnosed as adenocarcinoma. Most of patients (73 patients or 81.4%) had prostate volume (TAUS) > 30 cm3 with the median at diagnosis was 51 cm3 (38.3 – 104.4). Furthermore, the median of PSA for diagnosis was 234.4 (94.4 – 1720.3) ng/mL and the median of testosterone level  at  diagnosis  was  317  (10  -  384)  ng/dL.  In  conclusion,  most  patients  with  prostate  cancer  are  identified  as  adenocarcinoma  with  metastatic  stage.  In  general, the prostate cancer patients age more than 61 years old with prostate volume  (TAUS)  >  30  cm3.  In  addition,  prostate  volume  and  testosterone  level  can be routinely used as initial screening and periodic assessment to evaluate prognosis and disease progression.